Antifungal Activity of Essential Oil From Zanthoxylum armatum DC. on Aspergillus flavus and Aflatoxins in Stored Platycladi Semen - Li, Ting; Chen, Mingyang; Ren, Guangxi; Hua, Guodong; Mi, Jiu; Jiang, Dan; Liu, Chunsheng (Frontiers in Microbiology, 2021)
The major objective of this study was to evaluate the inhibitory effect of essential oil (EO) from Zanthoxylum armatum DC.(Z. armatum DC.) on Aspergillus flavus (A. flavus). The chemical composition of the EO was identified by Gas Chromatography-Mass Spectrometer (GC-MS).The minimum inhibitory concentration of EO was investigated by liquid fermentation. The morphology, colony number and aflatoxin content of A. flavus in platycladi semen were investigated by stereomicroscopy, scanning electron microscopy, plate counting and High Performance Liquid Chromatography (HPLC). The results indicated that the minimum inhibitory concentration of EO was 0.8 μL·mL-1, and the main components were β-phellandrene (7.53%), D-limonene (13.24%), linalool (41.73%), terpinen-4-ol (5.33%), and trans-nerolidol (6.30%). After the EO fumigated the platycladi semen, the growth of A. flavus slowed, and the mycelium shrank considerably. The number of colonies after EO treatment at room temperature and cold storage was significantly reduced, the inhibition effect was better under cold storage, and the aflatoxin B1 content did not exceed the standard within 100 days. Therefore, this study demonstrated the good potential of A. flavus growth inhibition during the storage of platycladi semen.